Basement Classification through Enhanced Magnetic Data Reductions in parts of Ekiti State, Southwestern Nigeria - Akingboye, Adedibu; Ogunyele, Abimbola (International Journal of Advanced Geosciences, 2017)
Enhanced magnetic data reductions via the use of various forms of filters were employed for basement classification in parts of Ekiti State. The data reductions and enhancement involve: reduction to equator (RTE), regional and residual, automatic gain control (AGC), downward continuation, upward continuations (1, 2, and 3 km), analytic signal (AS) and horizontal gradient (HG) to map and delineate basement rocks and structures, while surface relief and spectral plot were used to determine depth to top of magnetic sources. The images revealed that the study area is characterized by different lithologies. The rocks evinced lineaments and faults trending NE-SW (G–G’, H–H’, J–J’, K–K’), NNE-SSW, E-W (minor) and approximately N-S, while the dykes are in NW-SE, NNW-SSW directions. The analytic signal (AS) and horizontal gradient (HG) revealed high amplitude reversed Z-like shape as migmatite rocks, differentiating them from the two flanks with low amplitude signals as schist and quartzite schist of Ijero and Aramoko and the granitic intrusive within these migmatised rocks around Ijan, Gbonyin and Ise/Otun. The shaded relief and the spectral plot showed that the total depth to top of magnetic sources ranged from 20m to 1.8km for shallower and deeper sources respectively.